2014
DOI: 10.1002/cplu.201402066
|View full text |Cite
|
Sign up to set email alerts
|

PtM/Ba/Al2O3Ce0.6Zr0.4O2: Influence of Synergetic Interactions between Transition Metal and Platinum on NOx Storage and Reduction

Abstract: PtM/Ba/ACZ (M=Mn, Fe, and Co) and Pt/Ba/ACZ were prepared using Al2O3Ce0.6Zr0.4O2 (ACZ) as a support. XRD analysis shows Ce0.6Zr0.4O2 solid solution was formed in the ACZ support, and M addition results in a slight shift of the characteristic peaks of Ce0.6Zr0.4O2 to higher 2θ value. A strong interaction between Pt and the transition metals was confirmed by X‐ray absorption fine structure experiments. The effects of transition‐metal addition on NOx storage and reduction, sulfur resistance, and regeneration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…For all samples, NO x removal efficiency was lowered in comparison with SO 2 -absent samples, being ascribed to the competitive adsorption of SO 2 with NO x on the storage components. While, it is noted that the degree of sulfur poisoning was apparently retarded over Pt/Co/Ba/Al and Pt/Mn/Ba/Al catalysts, being consistent with previous report that Co, Mn addition could enhance the catalysts' sulfur resistance [37].…”
Section: Catalytic Propertiessupporting
confidence: 81%
“…For all samples, NO x removal efficiency was lowered in comparison with SO 2 -absent samples, being ascribed to the competitive adsorption of SO 2 with NO x on the storage components. While, it is noted that the degree of sulfur poisoning was apparently retarded over Pt/Co/Ba/Al and Pt/Mn/Ba/Al catalysts, being consistent with previous report that Co, Mn addition could enhance the catalysts' sulfur resistance [37].…”
Section: Catalytic Propertiessupporting
confidence: 81%
“…They found that the catalytic activity of CeO 2 was greatly enhanced by the support of CuO on CeO 2 owing to the synergistic catalytic effect at the CeO 2 and CuO phase interfaces 10. PtM/Ba/Al 2 O 3 Ce 0.6 Zr 0.4 O 2 was synthesized by Wang’s group and the strong synergetic interactions between the transition metal and platinum were found to be very important in NO x storage and reduction 11. Luo et al.…”
Section: Introductionmentioning
confidence: 99%